Mitigasi Banjir Kecamatan Sabbangparu, Kabupaten Wajo - Ian Fahrul Reza; Batara Surya; Emil Salim Rasyidi; Jamilah Abbas (Fakultas Teknik Universitas Bosowa, 2023)
The purpose of this study is to find out which locations are vulnerable to flooding in Sabbangparu District, Wajo Regency, then provide direction for flood disaster mitigation in Sabbangparu District, Wajo Regency. The variables used in this study are flood vulnerability variables which consist of flood disaster vulnerability, social vulnerability, physical vulnerability, economic vulnerability to environmental vulnerability and the flood disaster mitigation direction variable consists of structural and non-structural mitigation based on the vulnerability variable. The analytical method used is the flood vulnerability analysis method and the descriptive analysis method. Based on the results of the analysis of the flood disaster location, Sabbangparu District, Wajo Regency, most of the areas have a moderate level of vulnerability which dominates. The mitigation direction is the integration of lessons on disaster risk reduction into subjects so that people can be aware to be prepared from an early age, the construction of river embankments which until now has not been realized optimally, and the reconstruction of community facilities and infrastructure.